Implementation of Digital Archives for Teachers and Administrators at State Vocational School 16 Jakarta - Roni Faslah; Marsofiyati; Henry Eryanto (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
The purpose of this community service is training and workshop to guide and assist teachers, employees and students in introducing and understanding and implementing digital archive management with Windows Explorer, Microsoft Office Excel, Microsoft Office Word and PHP MYSQL.. The resulting output is a digital archive book that will be useful in guiding teachers and as one of the teaching materials in carrying out education and teaching in vocational high schools. The methodology used in the implementation of this community service activity is action research activities consisting of Planning, Preparation, Implementation (actions), Observation and Evaluation and Reflection. The conclusion of community service is the implementation of community service activities through guidance and assistance with the results of increased knowledge about digital archives, skills in managing digital archives, expertise in using digital information technology and being able to apply digital archives management and support for the course of an organization.